Social practices transformation: Peter Berger’s and Thomas Luckmann’s theory in crisis society - E D Osipova (RUDN journal of Sociology, 2015)
The article is devoted to Peter Berger’s and Thomas Luckmann’s theory of the construction of reality in the context of social practices transformation in the risk society. According to this theory, daily routine appears to be the basis of social reality that is interpreted as the result of the interaction processes. The article considers the fundamental procedures of the social reality construction - institutionalization and legitimization; such an analysis proves the famous sociologists idea that the daily routine is the foundation of social world. However, while analyzing daily routine practices we can see that the habitual behavior patterns are changing and new types of action are developing in the situation of the unstable and unpredictable crisis society. In the contemporary world, the habitual rational logic that we traditionally followed in everyday life to organize our behavior does not fulfill its functions. As a result, a special type of social consciences named catastrophic thinking is developing. Referring to the data of sociological studies the article considers the most striking examples of the social practices transformation and the new type of rational logic development, such as the changing attitudes to the health and the reviving interest to making a will in the contemporary world.